Effect of magnetic field treatment on the structural and aggregation behavior of gluten, gliadin, and glutenin in potato pulp enriched dough - Jialin Song; Feng Han; Ying Sun; Dongliang Zhang; Shanfeng Chen; Hongjun Li (Innovative Food Science & Emerging Technologies, 2026)

Bisphenol a exposure induces low back pain associated with intervertebral disc degeneration via BIRC3-mediated nucleus pulposus cell senescence - Tao Kang; Hongjun Huang; Dun Liu; Junfei Feng; Yongqi Huang; Song Wang; Hongyuan Xu; Yuwang Du; Zuyuan Huang; Rongqing He; Hua Jiang (Toxicology and Applied Pharmacology, 2026)

Extrusion-induced supramolecular disassembly of rice adjunct starch: governing enzymatic convertibility and fermentable sugar release in mashing - Lijun Jiang; Jialin Song; Mingming Qi; Jian Liu; Chengyi Sun; Bo Wang; Fengling Yue; Miaomiao Sui; Dongliang Zhang; Guihong Zhao; Hongjun Li (Food Chemistry, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

Liquid fuel intrusion causes carbon canister deterioration and excess evaporative VOC emissions from in-use vehicles - Pengfei Song; Yan Liu; Qiang Chen; Jingyu Liu; Xueying Zeng; Tianlong Xing; Rui Zhang; Chongzhi Zhong; Taiyu Zhang; Ning Yang; Jianfei Peng; Hongjun Mao (Journal of Hazardous Materials, 2026)

Bioaccumulation and trophic transfer of PAHs in the Yellow River Estuary food web: A fugacity-based model for ecological and human health risk assessment - Xin Liu; Xuguang Hong; Hongjun Song; Degang Wang; Kan Chen; Jiachen Sun; Zhaohui Zhang; Jiansong Chu (Marine Pollution Bulletin, 2026)

Escalating landscape fire exposure and its deteriorating global equity: Role of associated population changes, socioeconomic levels, and climate changes - Tong Pan; Hongjun Wang; Jiyuan Chen; Zipei Fan; Xuan Song (Science of The Total Environment, 2026)

Ammonia emission from real-world in-use vehicle fleets in a megacity in China - based on tunnel measurement - Jiliang Guo; Jinsheng Zhang; Ainan Song; Hui Tong; Jingchun Tang; Ning Yang; Zhuofei Du; Qijun Zhang; Ting Wang; Lin Wu; Jianfei Peng; Hongjun Mao (Journal of Environmental Sciences, 2026)

A modified curve number method for runoff prediction of different vegetation types at the slope scale in China - Jinle Yu; Hongjun Chen; Miaomiao Wang; Jiachi Bao; Wenyi Song; Xitong He; Wenhai Shi (Soil and Tillage Research, 2025)

Enhanced built-in electric field and strong interfacial electronic coupling in 2D/2D BiO2-x/Ti3C2 Schottky heterojunction boost exciton dissociation for sustainable molecular oxygen activation toward 100 % singlet oxygen generation - Chongyang Yang; Song Tian; Yanyan Liu; Liguo Shen; Cheng Chen; Yanchao Xu; Leihong Zhao; Bisheng Li; Mingzhu Zhou; Hongjun Lin (Journal of Environmental Chemical Engineering, 2025)

Ultrasound-assisted fermentation of doughs enriched with 7S and 11S soy protein fractions: impacts on quality and protein–protein interactions - Feng Han; Ying Sun; Jialin Song; Xin Zhang; Chuangshuo Yan; Yufan Wang; Shanfeng Chen; Chengye Ma; Hongjun Li (Food Research International, 2025)

Soil carbon dioxide dynamics in deep profiles under erosional and depositional conditions on the Chinese Loess Plateau - Jiachi Bao; Tiantian Chen; Wenyi Song; Miaomiao Wang; Hongjun Chen; Jinle Yu; Wenhai Shi (CATENA, 2025)

Unrecognized emissions and health risks of intermediate-volatility organic compounds in vehicle cabins: Insights from a nontargeted analytical approach - Haoning Chang; Yajun Wu; Jing Zhang; Dianjia Liu; Yao Zeng; Pengfei Song; Jinsheng Zhang; Yan Liu; Lin Wu; Ting Wang; Hongjun Mao; Jianfei Peng; et al. (Journal of Hazardous Materials, 2025)

Rethinking calibration as a statistical estimation problem to improve measurement accuracy - Song S. Qian; Sabrina Jaffe; Emanuela Gionfriddo; Hongjun Wang; Curtis J. Richardson; Nipunika H. Godage (Analytica Chimica Acta, 2025)

Excess vehicular evaporative emissions for prolonged parking during the COVID-19 lockdown in China - Pengfei Song; Jianfei Peng; Yan Liu; Chongzhi Zhong; Qiang Chen; Chao Zou; Shida Sun; Yajun Wu; Yao Gu; Taiyu Zhang; Ning Yang; Hongjun Mao (Journal of Hazardous Materials, 2025)

Prediction of fluid-thermal-structure interaction of three equilateral-triangular circular cylinders based on XGBoost-SHAP - Jiawen Zhong; Hongjun Zhu; Tongming Zhou; Shuigen Zhou; Jingze Song (Ocean Engineering, 2025)

Direct visual detection for methicillin-resistant Staphylococcus aureus in milk based on the RPA-Cas12a-LFS method - Yixiang Sun; Liren Zhang; Huimin Wu; Hongjun Chen; Huijie Hu; Chongyu Zhang; Xiaoqiang Li; Yuan Li; Yimai Wang; Liqiang Luo; Yizhi Song (Food Control, 2025)

A modified curve number method for runoff prediction of different soil types in China - Miaomiao Wang; Yangdong Zhao; Wenhai Shi; Jinle Yu; Tiantian Chen; Jiachi Bao; Wenyi Song; Hongjun Chen (CATENA, 2025)

Contribution of Vehicular Evaporative S/IVOC emission to SOA formation in China - Zhaoyang Fan; Yajun Wu; Yuwei Xie; Hui Tong; Naixiu Sun; Pengfei Song; Wentian Xu; Yan Liu; Shaojie Song; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2025)

A novel method to improve the anti-ageing ability of bitumen by organic LDHs/SBS composite: Preparation, performance evaluation and mechanism analysis - Canlin Zhang; Shuai Yang; Ting Wang; Song Xu; Peng Jin; Hongjun Dong; Yi Zhang; Yu Chen (Fuel, 2025)

Understanding the anti-browning mechanism and physicochemical properties in potato pulp during the magnetic field processing - Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Xin Zhang; Chuangshuo Yan; Yujian Xie; Dongliang Zhang; Hongjun Li (Food Chemistry, 2025)

Exploring the influence of extruded rice adjunct on wort separation efficiency: A bio-macromolecule degradation perspective - Lijun Jiang; Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Dongliang Zhang; Shifeng Yu; Hongjun Li (Food Chemistry, 2025)

An improved curve number for runoff prediction under different vegetation pattern at slope scale in China - Wenhai Shi; Miaomiao Wang; Jiachi Bao; Jinle Yu; Tiantian Chen; Wenyi Song; Hongjun Chen (CATENA, 2025)

Microplastic transport and ecological risk in coastal intruded aquifers based on a coupled seawater intrusion and microplastic risk assessment model - Guangquan Chen; Yinqiao Zou; Guiyao Xiong; Yancheng Wang; Wenqing Zhao; Xingyong Xu; Xiaobin Zhu; Jichun Wu; Fan Song; Hongjun Yu (Journal of Hazardous Materials, 2024)

A novel application of industrial waste bischofite for the anti-aging property of asphalt: Synthesis of organic layered double hydroxide and performance evaluation - Hongjun Dong; Canlin Zhang; Yiwei Weng; Ting Wang; Song Xu; Shijie Ma; Shuai Yang; Yu Chen (Journal of Cleaner Production, 2024)

Exploring source-specific ecological risks of PAHs near oil platforms in the Yellow River Estuary, Bohai Sea - Xin Liu; Xuguang Hong; Hongjun Song; Tong Zhang; Kan Chen; Jiansong Chu (Marine Pollution Bulletin, 2024)

Divergent chemical compositions of soil organic matter size fractions under long-term amendments across a climate gradient - Fanbo Song; Ning Hu; Yilai Lou; Huimin Zhang; Ping Zhu; Dongchu Li; Hongjun Gao; Shuiqing Zhang; Yidong Wang (Soil and Tillage Research, 2024)

Source-to-sink processes and genetic mechanism of progradational and lateral accretion submarine fans in the Qiongdongnan Basin, South China Sea - Congjun Feng; Guozhang Fan; Zhili Yang; Xingzong Yao; Xinglei Song; Weiqiang Li; Hongjun Qu; Qiang Zhang; Xuefeng Wang (Frontiers in Marine Science, 2024)
Submarine fan reservoirs are important accumulation zones for oil, gas, and natural gas hydrates, offering significant potential for hydrocarbon exploration. During the deposition period of the Sanya Formation in the southern part of the Changchang Sag of the Qiongdongnan Basin, a large submarine fan developed. However, the internal structure, source-sink system, and formation mechanism of this fan remain poorly understood, posing significant challenges to exploration in this area. This paper examines the source-to-sink sedimentary processes and deposition of submarine fans, using the Changchang Sag, in the Qiongdongnan Basin in the Northern South China Sea, as an example, which will provide valuable general guidance for deep water oil and gas exploration. Based on the theories of seismic stratigraphy and seismic sedimentology, this paper utilizes techniques such as seismic facies analysis, seismic attribute optimization, paleogeomorphology reconstruction, and source-to-sink sedimentary system analysis to analyze the 3D seismic data of the study area. Research indicates that the Sanya Formation in the Changchang Sag of the Qiongdongnan Basin comprises three depositional units: submarine fan, feeder channel, and Semi-deep marine to deep marine mudstone. The submarine fan is a fan formed by the coupling and convergence of submarine fans sourced from the southwest and southeast. Internally, it is divided into three sub-facies: the proximal fan of the sand-rich submarine fan, the main body of the sand-rich submarine fan lobes, and the distal lobes of the sand-rich submarine fan. The submarine fan sourced from the southwest extends nearly north-south and is primarily fed by sediment transported through three large, banded ancient valleys. The sedimentary filling is characterized by three-phase progradation. The submarine fan sourced from the southeast extends nearly east-west and is primarily fed by sediment transported through a single large, banded ancient valley. The sedimentary filling is characterized by two-phase lateral accumulation. During the deposition period of the Sanya Formation, certain areas of the southern uplift belt were exposed for extended periods and subjected to weathering and erosion. Sediments are transported to large ancient valleys through small supply channels. A large number of sediments were transported to the southern slope of the Changchang sag through the provenance channel system such as large ancient valleys and slope belts and deposited in the center of the sag. These make up a complete system of large ancient uplifts and submarine fan source-to-sink sedimentary systems.The sedimentary model is a lobed submarine fan controlled by semi-restricted ancient valleys and expansive basins.

Exhaust and evaporative volatile organic compounds emissions from vehicles fueled with ethanol-blended-gasoline - Ruikang Li; Chongzhi Zhong; Yang Ning; Yan Liu; Pengfei Song; Ruiguang Xu; Hongjun Mao (Environmental Pollution, 2024)

Surface plasmon enhancement of 1D Ag nanowires modified electro-treated BiVO4 photoanode with abundant oxygen vacancies for solar water oxidation - Song Zhang; Hongjun Zhang; Yuan Gu; Xinjie Mao; Xiaoying Gao; Dongbo Xu (Fuel, 2024)

Modelling to assess the suitability of hydrological-hydrodynamic model under the hydropower development impact in the Lancang-Mekong river basin - Xiaobo Yun; Jianing Song; Jie Wang; Hongjun Bao (Journal of Hydrology, 2024)

Microsatellite Analysis of the Influence of Sebastes schlegelii Restocking on the Genetic Structure of Stocks in Rongcheng Bay - Yi Zhang; Lijuan Wang; Zhihao Wu; Hongjun Liu; Zongcheng Song; Feng You (Thalassas: An International Journal of Marine Sciences, 2024)

Exploring Seasonal Variations in Fish Communities: A Study of the Yellow River Estuary and Its Adjacent Waters Using eDNA and Trawl Surveys - Xiaoyang Wang; Fan Li; Fei Shao; Hongjun Song; Na Song; Xiaomin Zhang; Linlin Zhao (Fishes, 2024)
The Yellow River Estuary and its adjacent waters serve as crucial spawning, foraging, and nursery areas for marine organisms, possessing abundant biological resources. Monitoring fish communities provides a baseline for implementing the sustainable utilization of marine resources. In this study, data were collected from 15 spring surface and bottom sites and 17 summer surface sites using eDNA and trawl surveys. The results showed that 37, 40, and 35 fish species were detected using eDNA in the spring (surface and bottom) and summer (surface), respectively, with 38 fish species caught during summer trawling. The dominant species mainly belonged to Engraulidae of Clupeiformes in the spring and Gobiidae of Perciformes in the summer, characterized by smaller-sized, short-lived, and pelagic fish species. The summer surface communities exhibited higher diversity than the spring surface and bottom communities. NMDS analysis revealed a degree of seasonal differences in fish communities and that there may be a lack of vertical stratification in the spring communities. The pH and DO were identified as the key environmental factors affecting the fish community. Additionally, the combination of eDNA and trawl surveys was regarded as a superior survey method. Our study provides valuable information for understanding seasonal fish communities in the Yellow River Estuary and its adjacent waters, contributing to fishery resource management and conservation in the region.

Atmospheric environment characteristic of severe dust storms and its impact on sulfate formation in downstream city - Naixiu Sun; Lin Wu; Fangyuan Zheng; Danni Liang; FuYuan Qi; Shaojie Song; Jianfei Peng; Yufen Zhang; Hongjun Mao (Science of The Total Environment, 2024)

Tailpipe volatile organic compounds (VOCs) emissions from Chinese gasoline vehicles under different vehicle standards, fuel types, and driving conditions - Peiji Liu; Yajun Wu; Zongxuan Li; Zongyan Lv; Jinsheng Zhang; Yan Liu; Ainan Song; Ting Wang; Lin Wu; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2024)

Transforming waste brake pads from automobiles into Nano-Catalyst: Synergistic Fe-C-Cu triple sites for efficient fenton-like oxidation of organic pollutants - Fuyuan Qi; Jianfei Peng; Zilu Liang; Jiliang Guo; Jiawei Yin; Ainan Song; Zongxuan Li; Jiayuan Liu; Tiange Fang; Jinsheng Zhang; Lin Wu; Qijun Zhang; et al. (Waste Management, 2024)

Synthesis of organic layered double hydroxide from waste bischofite and its application on ageing resistance of asphalt - Canlin Zhang; Hongjun Dong; Ting Wang; Yifei Li; Song Xu; Yun Que; Yu Chen (Fuel, 2024)

Understanding the degradation mechanisms of cyanide and starch in cassava flour during extrusion processing - Mingming Qi; Jialin Song; Lijun Jiang; Luxia Li; Mei Xu; Yueming Li; Shifeng Yu; Hongjun Li (Innovative Food Science & Emerging Technologies, 2024)

Dynamical graph neural network with attention mechanism for epilepsy detection using single channel EEG - Yang Li; Yang Yang; Qinghe Zheng; Yunxia Liu; Hongjun Wang; Shangling Song; Penghui Zhao (Medical & Biological Engineering & Computing, 2024)

Seasonal implications for taxonomic sufficiency to simplify M-AMBI methodology in the coastal area adjacent to a eutrophic estuary - Chenman Yang; Hongjun Song; Yi Sun; Pengfei Xie; Yuan Liu; Hongjun Li (Acta Oceanologica Sinica, 2023)

Dynamic simulation and analysis of land use competition patterns to support sustainable territorial spatial management: a case study of Shenyang City, Northeast China - Quanxi Wang; Ge Song; Gaofeng Ren; Hongjun Sui; Ruiqing Su (Environmental Science and Pollution Research, 2023)

Particulate emissions from gasoline vehicles using three different fuel injection technologies - Zongyan Lv; Jianfei Peng; Jinsheng Zhang; Lei Yang; Dongping Guo; Ning Wei; Yajun Wu; Tiange Fang; Ainan Song; Chaoyang Fan; Lin Wu; Qijun Zhang; et al. (Journal of Cleaner Production, 2023)

Evaluating vehicular exhaust and evaporative emissions via VOC measurement in an underground parking garage - Yajun Wu; Yan Liu; Peiji Liu; Luna Sun; Pengfei Song; Jianfei Peng; Ruikang Li; Ning Wei; Lin Wu; Ting Wang; Lina Zhang; Ning Yang; et al. (Environmental Pollution, 2023)

Material efficiency strategies across the industrial chain to secure indium availability for global carbon neutrality - Huiling Song; Chang Wang; Kun Sun; Hongjun Geng; Lyushui Zuo (Resources Policy, 2023)

Novel cetyltrimethylammonium bromide modified mixed adsorbent for efficient treatment of dyeing and printing wastewater - Zhenxiang Pan; Mohan Song; Bizhen Zeng; Liguo Shen; Leihong Zhao; Hongjun Lin (Process Safety and Environmental Protection, 2023)

Initiation and evolution of an isolated submarine canyon system on a low-gradient continental slope - Wei Li; Shuang Li; Tiago M. Alves; Song Jing; Hongjun Chen; Wenhuan Zhan (Geomorphology, 2023)

Modification mechanism of protein in rice adjuncts upon extrusion and its effects on nitrogen conversion during mashing - Lijun Jiang; Jialin Song; Mingming Qi; Wenjing Suo; Yuxin Deng; Yao Liu; Luxia Li; Dongliang Zhang; Chenjie Wang; Hongjun Li (Food Chemistry, 2023)

Surface selenation engineering on metal cocatalysts for highly efficient photoreduction of carbon dioxide to methanol - Wenbin Chen; Shijie Wu; Liyan Xie; Yujie Wu; Yanwen Ye; Huigang Wang; Zhulei Chen; Hongjun Lin; Leihong Zhao; Song Bai (Chemical Engineering Journal, 2023)

Distinct ecological mechanisms drive the spatial scaling of abundant and rare microbial taxa in a coastal sediment - Xia Liu; Hongjun Li; Wen Song; Qichao Tu (Journal of Biogeography, 2023)
Aim Revealing the ecological mechanisms driving the diversity patterns of microbial communities across space and through time is an essential issue in microbial biogeography. This study links microbial spatial scaling with ecological mechanisms, aiming to provide novel mechanistic insights into the biogeographic patterns followed by different types of microbes. Location Beibu Gulf, a semi‐enclosed oceanic bay located on the southern coast of China. Taxon Bacteria, which were further classified as abundant and rare taxa. Methods By employing high throughput sequencing, two typical spatial scaling models, diversity‐area (DAR) and distance‐decay relationships (DDR), were investigated for the abundant and rare microbial communities in a coastal sediment ecosystem. Both alpha‐ and beta‐diversity indices were extended to Hill numbers to verify the contribution of abundant and rare taxa to DAR and DDR. The iCAMP approach was used to quantify the contribution of different ecological processes in structuring microbial communities. Results Strong spatial scaling patterns were observed for the whole communities and the rare subcommunities but only weak patterns for the abundant subcommunities. Rare subcommunities were mainly responsible for the observed spatial scaling patterns, as confirmed by extending spatial scaling diversity metrics to Hill numbers. Both environmental heterogeneity and local community assembly mechanisms drove the spatial scaling of microbial communities. Strong ecological drift and dispersal limitation underlay the spatial scaling of rare subcommunities, whereas high homogeneous selection weakened the spatial scaling of abundant subcommunities. Main Conclusions Rare taxa were mainly responsible for the biogeographic patterns followed by sediment microbial communities in the Beibu Gulf. Distinct ecological mechanisms underlay the different biogeographic patterns followed by abundant and rare subcommunities.

Optical properties of vehicular brown carbon emissions: Road tunnel and chassis dynamometer tests - Chung Song Ho; Zongyan Lv; Jianfei Peng; Jinsheng Zhang; Tong-Hyok Choe; Qijun Zhang; Zhuofei Du; Hongjun Mao (Environmental Pollution, 2023)

Spatiotemporal variation of cultivated land ecosystem stability in typical regions of Lower Liaohe Plain China based on stress - buffer - response - Hongjun Sui; Ge Song; Wanying Liu; Yuxin Zhang; Ruiqing Su; Quanxi Wang; Gaofeng Ren; Yuqi Mi (Science of The Total Environment, 2023)

CircRNA3616 knockdown attenuates inflammation and apoptosis in spinal cord injury by inhibiting TLR4/NF-κB activity via sponging miR-137 - Li Wang; Zhiwen Song; Hongjun Zou; Haining Chen; Yong Hu; Xiangnan Li; Jinbo Liu (Molecular and Cellular Biochemistry, 2023)

Tunnel measurements reveal significant reduction in traffic-related light-absorbing aerosol emissions in China - Chung Song Ho; Jianfei Peng; Zongyan Lv; Bin Sun; Lei Yang; Jinsheng Zhang; Jiliang Guo; Qijun Zhang; Zhuofei Du; Hongjun Mao (Science of The Total Environment, 2023)

Stock Assessment of Hatchery-Released Clam Meretrix meretrix in an Estuary of China From the Perspectives of Population Ecology and Genetic Diversity - Anguo Zhang; Hongjun Li; Xiaolong Yang; Lili Wang; Yangchun Gao; Mingshan Song; Xiutang Yuan (Frontiers in Marine Science, 2021)
In this study, the release effects of the buried clam Meretrix meretrix in a northern estuary of China (Shuangtaizi Estuary) was assessed in terms of population ecology and genetic variability by using longer-term monitoring data from 2011 (used as the baseline data) to 2018. A total of 2.4 × 10 8 hatchery juveniles were released from 2012 to 2014, and follow-up monitoring survey of the growth, distribution, density, and biomass of M. meretrix population was carried out. Results showed a temporary spike in the population of M. meretrix , and the population underwent considerable year-to-year fluctuations in total abundance and biomass. Meanwhile, the age structure of the populations from 2011 to 2018 is still an unstable expanding type. Genetic analysis based on 10 polymorphic microsatellite markers revealed no significant genetic differentiation and weak genetic structures between years but higher genetic diversities in 2014–2018 than in the initial period (2013) of stock restoration. Our study suggests that effective policies for management and conservation to restore M. meretrix population by local governments are still needed in the long run.

Strong and regionally distinct links between ice‐retreat timing and phytoplankton production in the Arctic Ocean - Hongjun Song; Rubao Ji; Meibing Jin; Yun Li; Zhixuan Feng; Øystein Varpe; Cabell S. Davis (Limnology and Oceanography, 2021)
Recent rapid sea‐ice changes in the Arctic Ocean have been widely considered to alter phytoplankton bloom timing and primary production, but the magnitude and regionality of this effect remain unclear. Here, we examined the spatial patterns in bloom timing, bloom magnitude, and primary productivity in relation to ice‐retreat timing, using a combination of satellite observations and numerical modeling. We found distinct regional differences in how the phytoplankton bloom relates to ice‐retreat timing. In the Arctic shelf regions, earlier and stronger blooms follow earlier annual ice retreats and enhanced light availability. By contrast, in some parts of the central Arctic, especially in the Canada Basin, there have been weakened blooms and reduced primary production in recent years. This reduction is largely due to a chain reaction triggered by earlier ice‐melt and enhanced haline stratification, which further suppress vertical nutrient exchange and reduce surface nutrients in an already nutrient‐limited system. Recognizing and quantifying strong and regionally distinct links between sea‐ice retreat and primary production will improve spatiotemporal projections of biogeochemical cycles and trophic flows in Arctic marine ecosystems.

Strategies to solve the reverse inference fallacy in future MRI studies of schizophrenia: a review - Chuanjun Zhuo; Gongying Li; Xiaodong Lin; Deguo Jiang; Yong Xu; Hongjun Tian; Wenqiang Wang; Xueqin Song (Brain Imaging and Behavior, 2021)
Few advances in schizophrenia research have been translated into clinical practice, despite 60 years of serum biomarkers studies and 50 years of genetic studies. During the last 30 years, neuroimaging studies on schizophrenia have gradually increased, partly due to the beautiful prospect that the pathophysiology of schizophrenia could be explained entirely by the Human Connectome Project (HCP). However, the fallacy of reverse inference has been a critical problem of the HCP. For this reason, there is a dire need for new strategies or research “bridges” to further schizophrenia at the biological level. To understand the importance of research “bridges,” it is vital to examine the strengths and weaknesses of the recent literature. Hence, in this review, our team has summarized the recent literature (1995–2018) about magnetic resonance imaging (MRI) of schizophrenia in terms of regional and global structural and functional alterations. We have also provided a new proposal that may supplement the HCP for studying schizophrenia. As postulated, despite the vast number of MRI studies in schizophrenia, the lack of homogeneity between the studies, along with the relatedness of schizophrenia with other neurological disorders, has hindered the study of schizophrenia. In addition, the reverse inference cannot be used to diagnose schizophrenia, further limiting the clinical impact of findings from medical imaging studies. We believe that multidisciplinary technologies may be used to develop research “bridges” to further investigate schizophrenia at the single neuron or neuron cluster levels. We have postulated about future strategies for overcoming the current limitations and establishing the research “bridges,” with an emphasis on multimodality imaging, molecular imaging, neuron cluster signals, single transmitter biomarkers, and nanotechnology. These research “bridges” may help solve the reverse inference fallacy and improve our understanding of schizophrenia for future studies.

Evaluating Neurodevelopmental Consequences of Perinatal Exposure to Antiretroviral Drugs: Current Challenges and New Approaches - Jordan G. Schnoll; Brian Temsamrit; Daniel Zhang; Hongjun Song; Guo-li Ming; Kimberly M. Christian (Journal of Neuroimmune Pharmacology, 2021)

Decadal characteristics of the floating Ulva and Sargassum in the Subei Shoal, Yellow Sea - Jie Xiao; Shiliang Fan; Zongling Wang; Mingzhu Fu; Hongjun Song; Xiao Wang; Chao Yuan; Min Pang; Xiaoxiang Miao; Xuelei Zhang (Acta Oceanologica Sinica, 2020)

High levels of genetic diversity and connectivity of whitespotted conger Conger myriaster in the East China Coast - Congcong Zou; Lijuan Wang; Lingming Kong; Yingjun Wang; Zhihao Wu; Jianhe Xu; Aihuan Song; Hongjun Liu; Feng You (Marine Biodiversity, 2020)

A longitudinal study of brain volume changes in rhesus macaque model infected with SIV - Bonan Song; Yunfang Li; Jiaojiao Liu; Haifeng Mi; Dan Liu; Wei Wang; Jun Sun; Yuanyuan Wang; Hongjun Li (Journal of NeuroVirology, 2020)

Genetic Assessment of a Black Rockfish, Sebastes schlegelii, Stock Enhancement Program in Lidao Bay, China Based on Mitochondrial and Nuclear DNA Analysis - Lijuan Wang; Zhihao Wu; Yingjun Wang; Mengxia Liu; Aihuan Song; Hongjun Liu; Feng You (Frontiers in Marine Science, 2020)

A non-negative and high-resolution finite volume method for the depth-integrated solute transport equation using an unstructured triangular mesh - Ronghui Ye; Chenming Zhang; Jun Kong; Guangqiu Jin; Hongjun Zhao; Zhiyao Song; Ling Li (Environmental Fluid Mechanics, 2018)

Phytoplankton pigment pattern in the subsurface chlorophyll maximum in the South Java coastal upwelling system, Indonesia - Chunlei Gao; Mingzhu Fu; Hongjun Song; Lei Wang; Qinsheng Wei; Ping Sun; Lin Liu; Xuelei Zhang (Acta Oceanologica Sinica, 2018)

Pm61: a recessive gene for resistance to powdery mildew in wheat landrace Xuxusanyuehuang identified by comparative genomics analysis - Huigai Sun; Jinghuang Hu; Wei Song; Dan Qiu; Lei Cui; Peipei Wu; Hongjun Zhang; Hongwei Liu; Li Yang; Yunfeng Qu; Yahui Li; Teng Li; et al. (Theoretical and Applied Genetics, 2018)

Using regression models to evaluate the formation of trihalomethanes and haloacetonitriles via chlorination of source water with low SUVA values in the Yangtze River Delta region, China - Huachang Hong; Qianyun Song; Asit Mazumder; Qian Luo; Jianrong Chen; Hongjun Lin; Haiying Yu; Liguo Shen; Yan Liang (Environmental Geochemistry and Health, 2016)

Microalgal industry in China: challenges and prospects - Jun Chen; Yan Wang; John R. Benemann; Xuecheng Zhang; Hongjun Hu; Song Qin (Journal of Applied Phycology, 2016)

Synthesis, Luminescent Properties of aza-Boron-Diquinomethene Difluoride Complexes and Their Application for Fluorescent Security Inks - Long Gu; Rui Liu; Hong Shi; Qiang Wang; Guangliang Song; Xiaolin Zhu; Shidong Yuan; Hongjun Zhu (Journal of Fluorescence, 2016)

In vivo construction of tissue-engineered cartilage using adipose-derived stem cells and bioreactor technology - Hongjun Kang; Shibi Lu; Jiang Peng; Qiang Yang; Shuyun Liu; Li Zhang; Jingxiang Huang; Xiang Sui; Bin Zhao; Aiyuan Wang; Wenjing Xu; Quanyi Guo; et al. (Cell and Tissue Banking, 2015)

Glial Cell-Derived Neurotrophic Factor Attenuates Neuropathic Pain in a Mouse Model of Chronic Constriction Injury: Possible Involvement of E-cadherin/p120ctn Signaling - Cunjin Wang; Hongjun Wang; Jun Pang; Li Li; Suming Zhang; Ge Song; Na Li; Junping Cao; Licai Zhang (Journal of Molecular Neuroscience, 2014)

NCAM Signaling Mediates the Effects of GDNF on Chronic Morphine-Induced Neuroadaptations - Li Li; Junping Cao; Suming Zhang; Cunjin Wang; Jinfeng Wang; Ge Song; Hongjun Wang; Licai Zhang (Journal of Molecular Neuroscience, 2014)

On the Fourier approximation method for steady water waves - Hongjun Zhao; Zhiyao Song; Ling Li; Jun Kong (Acta Oceanologica Sinica, 2014)

On the universal third order Stokes wave solution - ZhiYao Song; HongJun Zhao; Ling Li; GuoNian Lü (Science China Earth Sciences, 2013)

Seasonal variability of the zooplankton community in the southwest of the Huanghai Sea (Yellow Sea) Cold Water Mass - Ping Liu; Hongjun Song; Xiao Wang; Zongling Wang; Xinming Pu; Mingyuan Zhu (Acta Oceanologica Sinica, 2012)

An extended time-dependent numerical model of the mild-slope equation with weakly nonlinear amplitude dispersion - Hongjun Zhao; Zhiyao Song; Fumin Xu; Ruijie Li (Acta Oceanologica Sinica, 2010)